The Impact of Resistanceand Aerobic Exerciseson Blood Sugar Level in Type 2 Diabetes Mellitus: Apilot Study (Medico Legal Update, 2021)
Objective: To rule out theimpact of resistanceand aerobic exerciseson sugar level in the blood in type 2diabetes mellitus population.Sample: 10 subjects who have type 2 diabetes mellitus comes under this study.Method: 10 subjects having type 2 diabetes mellitus were taken to control and experimental sets.Experimental set received aerobic and resistance exercise training program as well as medication whilecontrol set received only medication for 4 weeks (6 weeks per day).Results: Paired t-test was used, and it was found that blood sugar was reduced in experimental set and twosample t-test was used to check between the group analyses and between set comparison it was found thatthere was no significant difference detected in sugar level in the blood.Conclusion: It was concluded that resistanceand aerobic exercises are beneficial for lowering the bloodglucose level in type 2 diabetes mellitus population.